Mengikis Segregasi Sastra Indonesia Keturunan Tionghoa - Suyadi Suyadi (Balai Bahasa Provinsi Bali, 2024)
This article aims to prevent the marginalization of Indonesian literature towards authors of Tionghoa descent. The marginalization (segregation) of Tionghoa circles is not only in residential areas, but also on the map of Indonesian literary history. This qualitative descriptive research was carried out using a historical approach. From literature studies and descriptive analysis it is known that the marginalization of Indonesian literary works of Tionghoa descent is determined by five factors, namely historical factors, sociological factors, political factors, economic factors and aesthetic factors. This research concludes that Indonesian-Tionghoa literature should be included in books on the history of Indonesian literature and that its authors should be given a place and space in the pluralistic Indonesian cultural treasures, side by side with other ethnicities. Like a garden, Indonesia will be beautiful if various flowers grow in it and bloom. Therefore, this article also recommends that Indonesian-Tionghoa literature be included in the educational curriculum in secondary schools and universities. AbstrakArtikel ini bertujuan agar tidak lagi terjadi marginalisasi sastra Indonesia terhadap pengarang keturunan Tionghoa. Peminggiran (segregasi) kalangan Tionghoa bukan saja berada di kawasan permukiman, tetapi juga dalam peta sejarah sastra Indonesia. Penelitian deskriptif kualitatif ini dilakukan dengan pendekatan sejarah. Dari studi pustaka dan analisis deskriptif diketahui bahwa marginalisasi terhadap karya-karya sastra Indonesia keturunan Tionghoa ditentukan oleh lima faktor, yaitu faktor historis, faktor sosiologis, faktor politik, faktor ekonomi, dan faktor estetik. Penelitian ini menyimpulkan agar sastra Indonesia-Tionghoa ini dimasukkan dalam buku-buku sejarah sastra Indonesia serta penulisnya diberikan tempat dan ruang dalam khazanah budaya Indonesia yang pluralis, berdampingan dengan etnis lain. Ibarat sebuah taman, Indonesia akan indah kalau di dalamnya tumbuh beraneka bunga nan bermekaran. Karena itu, artikel ini juga merekomendasikan agar sastra Indonesia-Tionghoa ini dimasukkan dalam kurikulum pendidikan di sekolah-sekolah tingkat menengah dan perguruan tinggi.